Kategorija sočutja v esejistiki Zbigniewa Herberta - Kopczyk, Michał (Slavistična revija, 2012)
The subject of this analysis is the essayistic work of Zbigniew Herbert (1924-1998), which has been known in Slovenia by virtue of the successful translations by Jana Unuk, Jasmina Šuler Galos, and Niko Jež. The author of this paper examines meanings which Herbert attributed to the concept of compassion. At the same time, he notices that a sympathetic attitude of the essays under consideration is an important perspective for the character, from which he validates selected phenomena in the history of western culture. The essayist focuses on cultures or organizations that were treated particularly harshly by history (the Minoan culture, the Albigensian culture, the Order of the Temple, and others). However, artistic endeavor remained at the center of Herbert's interest. The narratives of Herbert's aesthetic fascination generally range from a "shock", great fascination, which sometimes surges to a sudden epiphany-to painstaking factographic studies. For this reason, curiosity awakened by an "encounter" with a masterpiece urges the essayist to explain the experience he came to participate in. This in most cases involves an attempt to determine a broader context of the experience. The point of reference for the author's conclusions includes, among others, the philosophy of Richard Rorty, who in his book Contingency, Irony, and Solidarity (1989) proposes that the basis for solidarity among people lies in the feeling that all human condition is similar.
Keywords: compassion; empathy; empatija; eseji; essay; Herbert, Zbigniew, 1924-1998; literarne študije; Polish literature; poljska književnost; Rorty, Richard, 1931-2007; sočutje